Racial disparities affect the association between gestational urinary phthalate mixtures and infant genital measures - Varde, Meghana; Newman, Roger B.; Wenzel, Abby G.; Kucklick, John R.; Wineland, Rebecca J.; Brock, John W.; Bloom, Michael S. (Frontiers in Reproductive Health, 2023)
Background: Phthalates are ubiquitous anti-androgenic endocrine disrupting chemicals found in personal care products, medications, and many plastics. Studies have shown a racial disparity in phthalates exposure among U.S. women, which may also impact fetal development. Methods: We conducted a prospective cohort study of gestational exposure to a phthalates mixture in a racially-diverse population to determine their association with genital development. Mid-gestation (18-22 weeks) urine was collected from 152 women who self-identified as non-Hispanic Black and 158 women who self-identified as non-Hispanic White in Charleston, South Carolina between 2011-2014. We measured eight phthalate monoester metabolites in urine using liquid chromatography tandem-mass spectrometry. Mid-gestational penile dimensions were measured using ultrasound and anogenital distances were measured postnatally. We used Bayesian kernel machine regression to estimate the associations among the mixture of phthalate metabolites and mid-gestation penile dimensions and postnatal anogenital distance measures among singleton male (n = 179) and female (n = 131) infants, adjusted for urinary specific gravity, maternal age, body mass index, education level, cigarette smoking, and gestational age at enrollment or birth weight z-score. Results: We found a stronger association between greater phthalates and decreased anopenile distance among infants born to women who self-identified as Black. Mono (2-ethylhexyl) phthalate (MEHP) was the driving mixture component among Black women, and monobutyl phthalate (MBP) and monoethyl phthalate (MEP) were drivers among White women. We also identified a non-linear association between phthalates and lesser ultrasound penile volume among women who self-identified as Black with monoisobutyl phthalate (MiBP) and MBP being most important. We also found an association between greater phthalates and shorter anoclitoral distance among infants born to women who self-identified as Black with MEP and monobenzyl phthalate (MBzP) contributing most to this association. Conclusion: Our results suggest a disparity in the association between gestational exposure to a mixture of phthalates and fetal genital development among women who self-identified as Black compared to White.